Orthotopic liver transplantation for Management of a Giant Liver Hemangioma: a case report and review of literature - Eghlimi, Hesameddin (BMC Surg, 2020)
BACKGROUND: Hepatic hemangioma (HH) is the most common benign tumor of the liver. In special conditions such as rapidly growing tumors, persistent pain, hemorrhage and when pressure effect on adjacent organs exist treatment is indicated. Surgical management is the most common treatment for HH. CASE PRESENTATION: A 38-year-old male patient was diagnosed with HH for 7 years. The initial presentation of the mass was progressive abdominal distention causing early satiety, gastro-esophageal reflux disease, vomiting, dysphagia and weight loss. Later, the patient developed bilateral lower extremity edema. Imaging with computed tomography (CT scan) showed a large mass measuring 32.4*26*3.1 cm which was considered unresectable. The patient underwent a deceased donor liver transplantation. The excised mass was 9 kg. After nine days of hospitalization the patient was discharged in good condition. Three months later, the patient was admitted due to fever and cytomegalovirus infection for which he received intravenous ganciclovir and was discharged. In the latest follow-up the patient had no liver or kidney dysfunction eight months after the transplantation. CONCLUSION: With appropriate patient selection, liver transplantation can be considered as a treatment option for patients with huge HHs which are life-threatening and surgically unresectable.